Encountering Jesus Christ in India: An Alternative Way of Doing Christology in a Cry-for-Life Situation Based on the Writings of George M. Soares-Prabhu - Vaidyakkaran, Sinto (Journal of Dharma, 2008)
Joseph Lobo, Encountering Jesus Christ in India: An Alternative Way of Doing Christology in a Cry-for-Life Situation Based on the Writings of George M. Soares-Prabhu, Bangalore: Asian Trading Corporation, 2004, pages: xv + 481, ISBN: 81-7086-358-9.